Genetics of serum BDNF: Meta-analysis of the Val66Met and genome-wide association study. (December 2013) - Terracciano, Antonio; Piras, Maria Grazia; Lobina, Monia; Mulas, Antonella; Meirelles, Osorio; Sutin, Angelina R.; Chan, Wayne; Sanna, Serena; Uda, Manuela; Crisponi, Laura; Schlessinger, David
Abstract Objectives. Lower levels of serum brain derived neurotrophic factor (BDNF) is one of the best known biomarkers of depression. To identify genetic variants associated with serum BDNF, we tested the Val66Met (rs6265) functional variant and conducted a genome-wide association scan (GWAS). Methods. In a community-based sample (N = 2054; aged 19–101, M = 51, SD = 15) from Sardinia, Italy, we measured serum BDNF concentration and conducted a GWAS. Results. We estimated the heritability of serum BDNF to be 0.48 from sib-pairs. There was no association between serum BDNF and Val66Met in the SardiNIA sample and in a meta-analysis of published studies (k = 13 studies, total n = 4727, P = 0.92). Although no genome-wide significant associations were identified, some evidence of association was found in the BDNF gene (rs11030102, P = 0.001) and at two loci (rs7170215, P = 4.8 × 10–5 and rs11073742 P = 1.2 × 10–5) near and within NTRK3 gene, a neurotrophic tyrosine kinase receptor. Conclusions. Our study and meta-analysis of the literature indicate that the BDNF Val66Met variant is not associated with serum BDNF, but other variants in the BDNF and NTRK3 genes might regulate the level of serum BDNF.